The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4102/sajhivmed.v19i1.771
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antenatal rapid human immunodeficiency virus testing in rural South Africa

Abstract: Introduction: South African guidelines recommend two rapid tests for diagnosing human immunodeficiency virus (HIV) using the serial HIV testing algorithm, but the accuracy and compliance to this algorithm is unknown in rural clinics. We evaluated the accuracy of HIV rapid testing and the time to receiving test results among pregnant women in rural KwaZulu-Natal (KZN).Method: We observed the accuracy of rapid HIV testing algorithms for 208 consenting antenatal patients accessing voluntary HIV testing services i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Consistent with our finding, evaluations by Jones et al [48] in 2019 on implementation of PMTCT policies (2013-2016) found that the highest proportions (around 60%) of facilities in rural SA reported no stock-outs of HIV test kits in the year before the survey [48]. However, contrary findings were reported by two studies in SA; a qualitative study [41] conducted in Durban, Cape Town and EC (2012-2013) and a survey [24] in rural PHC facilities in KZN (2015KZN ( -2016. These studies identified HIV test kits stockout as a major barrier which resulted in poor compliance with testing guidelines, with some testers having to adapt HIV rapid testing algorithms [24,41] or to refer clients to nearby facilities [41].…”
Section: Plos Onesupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with our finding, evaluations by Jones et al [48] in 2019 on implementation of PMTCT policies (2013-2016) found that the highest proportions (around 60%) of facilities in rural SA reported no stock-outs of HIV test kits in the year before the survey [48]. However, contrary findings were reported by two studies in SA; a qualitative study [41] conducted in Durban, Cape Town and EC (2012-2013) and a survey [24] in rural PHC facilities in KZN (2015KZN ( -2016. These studies identified HIV test kits stockout as a major barrier which resulted in poor compliance with testing guidelines, with some testers having to adapt HIV rapid testing algorithms [24,41] or to refer clients to nearby facilities [41].…”
Section: Plos Onesupporting
confidence: 88%
“…However, contrary findings were reported by two studies in SA; a qualitative study [41] conducted in Durban, Cape Town and EC (2012-2013) and a survey [24] in rural PHC facilities in KZN (2015KZN ( -2016. These studies identified HIV test kits stockout as a major barrier which resulted in poor compliance with testing guidelines, with some testers having to adapt HIV rapid testing algorithms [24,41] or to refer clients to nearby facilities [41]. Focused continuous quality improvement (CQI) interventions including technical on-site mentoring have shown to remarkably improve PMTCT data quality [42,43].…”
Section: Plos Onementioning
confidence: 77%
See 1 more Smart Citation
“…1,2 HIV rapid testing services allow people diagnosed with HIV to be linked appropriately and on timely manner to treatment and care services. 3,4 The World Health Organization (WHO) established quality standards for the implementation of HIV rapid testing ser-vices in order to ensure the quality of testing services. 5 Such standards include: personnel training and certification; physical facility (such as room, hand washing facilities, waste management equipment, light source, cabinets for storage of equipment's and registers); and safety practices (such as availability and use of PPEs, availability and use of job aids and SOPs for safety as well as hand washing during provision of services).…”
Section: Introductionmentioning
confidence: 99%